BAY 81‐8973, a full‐length recombinant factor VIII: manufacturing processes and product characteristics. Issue 2 (19th December 2016) - Garger, S.; Severs, J.; Regan, L.; Hesslein, A.; Ignowski, J.; Wu, P.; Long, E.; Gupta, S.; Liu, S.; Wang, W.
Abstract : BAY 81‐8973 (Kovaltry ®, Bayer, Berkeley, CA, USA) is an unmodified, full‐length recombinant human factor VIII (FVIII) approved for prophylaxis and on‐demand treatment of bleeding episodes in patients with haemophilia A. The BAY 81‐8973 manufacturing process is based on the process used for sucrose‐formulated recombinant FVIII (rFVIII‐FS), with changes and enhancements made to improve production efficiency, further augment pathogen safety, and eliminate animal‐ and human‐derived raw materials from the production processes. The baby hamster kidney cell line used for BAY 81‐8973 was developed by introducing the gene for human heat shock protein 70 into the rFVIII‐FS cell line, a change that improved cell line robustness and productivity. Pathogen safety was enhanced by including a 20‐nm filtration step, which can remove viruses, transmissible spongiform encephalopathy agents and potential protein aggregates. No human‐ or animal‐derived proteins are added to the cell culture process, purification or final formulation. The BAY 81‐8973 manufacturing process results in a product of enhanced purity with a consistently high degree of sialylation of N‐linked glycans on the molecular surface. The innovative manufacturing techniques used for BAY 81‐8973 yield an effective rFVIII product with a favourable safety profile for treatment of haemophilia A.